Clean mobility and intelligent transport systems - Fiorini, Michele; Lin, Jia-Chin (London, United Kingdom The Institution of Engineering and Technology, 2015)
This book provides an overview of current topics in intelligent and green transportation on land, sea and in flight, with contributions from an international team of leading experts. A wide range of chapters discuss: the importance of Intelligent Transport Systems (ITS); ICT for intelligent public transport systems; ITS and freight transport; energy-efficient and real-time database management techniques for wireless sensor networks; proactive safety - cooperative collision warning for vehicles; electronic toll collection systems; business models and solutions for user-centered intelligent transport systems; digital infrastructures for increased safety, efficiency and environmental sustainability in shipping logistics; integrated visual information for maritime surveillance; automatic identification system (AIS) AIS signal radiolocation, tracking and verification; the impact of satellite AIS to the environmental challenges of modern shipping; how green is e-Navigation?; optimal ship operation: monitoring technology of ship overall heat balance; regulation of ship-source pollution through international convention regimes; foresight application for the transport sector; and trends in aeronautical air ground communications.
Electronic reproduction.
Keywords: Database management; Mobile communication systems; Radio direction finders; Ships; Wireless sensor networks; Electronic books